POPULARITAS SINDHEN (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
Apparently, the sindhèn life, today, have not been far from celebrities one or otherarties with many other styles and beautiful tricked performances. Therefore, it isnatural, that every sindhèn always wants to be popular, famous, and amazed bymany people with the result that they can do the ways to reach what they wantto. But, how to be a sindhèn, what trick to get to become a popular sindhèn, andhow to hold their existence so that they constantly get interest of wide society.The questions above will be answered in this article which is a research result ofpopular sindhèn in Semarang by using quantitative paradigm. First, the ways tobe a sindhèn has four factors, namely the way to learn, its surrounding, socialassociate, and laku brata. Second, the sindhèn popularity is appeared from theirhigh stage-performance (20 to 25 times per month), the stage area reach out ofprovince, quality of artistic trough their special style, having wide influentialsponsor, and getting compensation between four to five millions each their stage.Third, the ways of sindhèn to maintain their attractive power for society attentionare taken on such as : (1) maintaining pattern and increasing quality and itscharacteristic, namely trough the colour of their soft voices, making gregel andwiledan so that their voices always impress such as tregel, rongêh, renyah, and berakfor the listeners; (2) they must be self confidence in pesindhênan, there is no otherjob except the sindhèn , such as langgam, campursari, and keroncong dangdut; (3)they must plait together social relation to the people who have wide influence aswell as art organisations; (4) they always surrender to the god trough laku brataas their belief.Key word: sindhén, popularitas